Breaking the Semi‐Quinoid Structure: Spin‐Switching from Strongly Coupled Singlet to Polarized Triplet State. Issue 38 (31st July 2014) - Ravat, Prince; Teki, Yoshio; Ito, Yoshikazu; Gorelik, Elena; Baumgarten, Martin
Abstract 2, 7‐TMPNO (4, 5, 9, 10‐tetramethoxypyrene‐2, 7‐bis(tert‐butylnitroxide)) was found to exist in semi‐quinoid form with unprecedented strong intramolecular magnetic exchange interaction of 2 J/kB=1185 K operating over a distance of 10 Å. Structural transformations with the activation energy of ΔEeq=949 K were observed by varying the temperature, from more quinoid structure at low temperature to more biradicaloid structure at higher temperature. Moreover, this molecule undergoes a transient spin transition from singlet to polarized triplet state upon photoexcitation revealed by TREPR spectroscopy. The spin Hamiltonian parameters were determined to be S=1, g=2.0065, D=−0.0112 cm−1, and E=−0.0014 cm−1 by spectral simulation with the hybrid Eigenfield/exact diagonalization method.